2021
DOI: 10.1002/lio2.690
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with anosmia recovery rate in COVID‐19 patients

Abstract: Objectives: The present study aimed to assess the 4-and 8-week recovery rate of anosmia and determine the factors associated with recovery in COVID-19 patients. Method: This retrospective study was conducted from December 2020 to March 2021. RT-PCR-proven COVID-19 adult patients (over 18 years of age) with a positive history of anosmia were included in this study. Anosmia was assessed based on the COVID-19 Anosmia Reporting Tool. The recovery rate of anosmia after 4 and 8 weeks were evaluated, and the relation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 30 publications
1
12
0
Order By: Relevance
“…In our study, a multiple logistic regression model associated higher ages (OR = 0.20; 95% CI: [0.07, 0.56], p = 0.002) and a duration of loss of smell longer than four weeks (OR = 0.27; 95% CI: [0.10, 0.76], p = 0.013) with a higher risk of persistent dysfunction. We did not find any association between the presence of comorbidities and the persistence of a chemosensory impairment, in concordance with previous studies, where the prevalence of comorbidities was even higher than that of 12.8% found in our study [ 23 , 28 , 29 , 44 ]. In addition, the analysis of the effects of other nasal and systemic symptoms during the infection has led to divergent results in different studies.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In our study, a multiple logistic regression model associated higher ages (OR = 0.20; 95% CI: [0.07, 0.56], p = 0.002) and a duration of loss of smell longer than four weeks (OR = 0.27; 95% CI: [0.10, 0.76], p = 0.013) with a higher risk of persistent dysfunction. We did not find any association between the presence of comorbidities and the persistence of a chemosensory impairment, in concordance with previous studies, where the prevalence of comorbidities was even higher than that of 12.8% found in our study [ 23 , 28 , 29 , 44 ]. In addition, the analysis of the effects of other nasal and systemic symptoms during the infection has led to divergent results in different studies.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, the analysis of the effects of other nasal and systemic symptoms during the infection has led to divergent results in different studies. Whereas some authors relate these symptoms to worsened results in the recovery of smell and taste both in the short and long term [ 26 , 39 , 43 , 44 ], others have not found any such relation [ 31 , 35 , 38 ]. In our study, we have shown that suffering from fever at the baseline was independently associated with a higher odds ratio for chemosensory recovery (OR = 3.19; 95% CI: [1.28, 7.94], p = 0.0126).…”
Section: Discussionmentioning
confidence: 99%
“…It is believed that nasal congestion causes “conductive” olfactory disorders due to coronavirus infection [ 16 ]. While a study stated nasal symptoms are statistically significant with smell and taste loss [ 28 ], this is in contrast to the study by Babaei et al [ 15 ] which stated that the presence of nasal discharge was not correlated with olfactory dysfunction. Shortness of breath: Shortness of breath is often found in severe COVID-19 symptoms.…”
Section: Discussionmentioning
confidence: 62%
“…Several researchers have hypothesized that the central mechanism of trigeminal damage occurs due to the connection of the olfactory system with the trigeminal nerve itself, with overlapping activation in areas such as the piriform cortex, ventral insula, and medial frontal gyrus [ 35 ]. Cigarette smoking: Cigarette smoking is a predictor of recovery of olfactory function 4 weeks after coronavirus infection [ 15 ]. Several researchers have cited lower rates of COVID-19 infection among individual smokers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation